The reduction of heparan sulphate in the glomerular basement membrane does not augment urinary albumin excretion. Issue 1 (8th July 2017) - Aoki, Satoshi; Saito-Hakoda, Akiko; Yoshikawa, Takeo; Shimizu, Kyoko; Kisu, Kiyomi; Suzuki, Susumu; Takagi, Kiyoshi; Mizumoto, Shuji; Yamada, Shuhei; van Kuppevelt, Toin H; Yokoyama, Atsushi; Matsusaka, Taiji; et al.
Abstract: Background: Heparan sulphate proteoglycan (HSPG) is present in the glomerular basement membrane (GBM) and is thought to play a major role in the glomerular charge barrier. Reductions and structural alterations of HSPG are observed in different types of kidney diseases accompanied by proteinuria. However, their causal relations remain unknown. Methods: We generated podocyte-specific exostosin-like 3 gene ( Extl3 ) knockout mice ( Extl3KO ) using a Cre-loxP recombination approach. A reduction of HSPG was expected in the GBM of these mice, because EXTL3 is involved in its synthesis. Mice were separated into three groups, according to the loads on the glomeruli: a high-protein diet group, a high-protein and high-sodium diet group and a hyperglycaemic group induced by streptozotocin treatment in addition to maintenance on a high-protein and high-sodium diet. The urinary albumin:creatinine ratio was measured at 7, 11, 15 and 19 weeks of age. Renal histology was also investigated. Results: Podocyte-specific expression of Cre recombinase was detected by immunohistochemistry. Moreover, immunofluorescent staining demonstrated a significant reduction of HSPG in the GBM. Electron microscopy showed irregularities in the GBM and effacement of the foot processes in Extl3KO . The values of the urinary albumin:creatinine ratio were within the range of microalbuminuria in all groups and did not significantly differ between the control mice and Extl3KO . Conclusions: The reduction of HSPG in the GBM did not augment urinary albumin excretion. HSPG's anionic charge appears to contribute little to the glomerular charge barrier.